Effects of the Construction of an Educational Mathematics Game on Students' Attitudes and Learning: Case Study - Paula Sofia Nunes; Armando A. Soares; Paula Catarino (Universidad Autónoma de Madrid, 2018)
This work describes the process of conception and development of an educational game of mathematics called "Mathematical Trivial", by students of the eighth grade of schooling, in a public school in Portugal. The game allows to practice the most varied mathematical contents through small adaptations, in any year of elementary education. In this work, we investigated whether the design of an educational game promotes the learning of mathematical concepts and identified the implications of students' attitudes towards mathematics. The methodology used was a case study design. This is a mixed case study because there is a combination of tools and techniques associated with qualitative and quantitative studies. The data collection was done through naturalistic observation, the application of tasks and the application of a questionnaire survey. Statistical analysis of the data was performed using spss software. The results suggest that the use of the educational game, as a resource to support the classes, produces a significant improvement of the students 'attitudes towards mathematics, as well as, it contributes to develop students' motivation. In addition, the process of constructing the educational game points to an improvement in the learning of geometrical concepts inherent to the game, in a playful and dynamic way.